AMERICAN SLANG FOUND IN DESPICABLE ME 3 MOVIE - Mailisa, Cici; Merina, Yola; Siska (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Nasional, 2022)
Slang is an informal language that is often used and known by a particular community or society. In this study, the researcher seeks to find out the types of slang and also find out how the functions of slang are used. In this analysis, researchers rely on Despicable Me 3 as a data source. It is from this film that the data are collected and adapted to the theory that focuses on type and function by Allan and Buridge (2006). To compile the results, the researcher used a qualitative descriptive method. In collecting data, several stages have been carried out such as watching the film, citing the data, and reviewing it in an effort to adapt it to the theory. As a result, three types of slang were found, namely Fresh and Creative, Flippant, and Imitative. Other types such as clipping and acronym could not be found. Then the researcher observed 5 functions which can also be found in this film, they are to address, to humiliate, to express impression, to initiate and to show intimacy.